Improving the organization of elections : a 2006 perspective : the integrationist - Dundas, Carl (Ian Randle KingstonJM, 2006)
Looks at what it takes for an emerging democracy to get the organization of elections right. Seeks to identify those practical steps that are necessary to deliver acceptable elections.